Public communication in the Region of Madrid about health and climate change: Fragmentation, decontextualization and individual responsibility - Vázquez Tarrío, Iván (Revista Española de Comunicación en Salud, 2025)
Introduction: To develop awareness among citizens on the deep relationship between socioeconomical model, climate change and health is a key element in tackling effective environmental and health policies. Objectives: This study plans to analyse if the communication policies address to the citizenship by the regional government of Madrid incorporate the deep interlinkage between socioeconomical model, climate change and health. Methodology: For that purpose, this work mainly focuses on the analysis of the discourses transmitted through the webpages belonging to the competent bodies in Health, Environment and Consumption. Results: The research performed reveals that the regional government of Madrid do not offer a frame that attends to the anthropogenic origin of climate change and its impact in the human health and introduce basically adaptation and mitigation solutions mainly based in individual action and responsibility. Conclusion: It is urgent, that government institutions offer to the citizenship a more holistic and transformative frame that integrate clime change in a public health context.